Measurement of the top quark mass with the template method in the [Formula: see text] channel using ATLAS data - ATLAS Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdelalim, A A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2012)
The top quark mass has been measured using the template method in the [Formula: see text] channel based on data recorded in 2011 with the ATLAS detector at the LHC. The data were taken at a proton-proton centre-of-mass energy of [Formula: see text] and correspond to an integrated luminosity of 1.04 fb-1. The analyses in the e+jets and μ+jets decay channels yield consistent results. The top quark mass is measured to be mtop=174.5±0.6stat±2.3syst GeV.